Carga combustible y su influencia en el riesgo de incendio en la unidad educativa Rumiñahui de Ambato, 2015.” plan de prevención de daños materiales y pérdidas humanas. - Sánchez Gavilanes, Edwin Roberto (2016)
The current research work is based on the study of fuel charge and your incidence on the risks of fires at Rumiñahui High School of Ambato, It being with the elaboration of diagnostic of the institution, location of existing resources, inventory, continuing with the analysis and quantification of fuel charge in the installations of the High school, besides the fuel charge that bring the trees existing on the place, To complete the study, one proceeds to the analysis of fire risk where Meseri method is used. The hypothesis tested in this study is the amount of the fuel charge at Rumiñahui High School of Ambato carry risk of fires The results determined that the risks of fires as a proposed design a preventive plan structured. The proposed scheme provides all preventive measures to be developed to avoid such incidents.